1998
DOI: 10.1046/j.1365-3008.1998.00017.x
|View full text |Cite
|
Sign up to set email alerts
|

Squirrel monkeys in Costa Rica: drifting to extinction

Abstract: Central American squirrel monkeys Saimiri oerstedii are limited to Costa Rica and Panama, and have never been abundant. The Costa Rican population is now decimated. Based on our survey of squirrel monkeys throughout a large portion of the Costa Rican range of this species in 1996, we can confirm that at least 1246 squirrel monkeys remain in 26 spatially dispersed localities. Despite probable undercounts of squirrel monkeys within sites and potentially missed localities, the total population size should be cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 12 publications
0
20
0
1
Order By: Relevance
“…The survival of the squirrel monkey in Panamá depends on management practices that may include restoring the habitat, relocations, and the administration of the isolated and highly reduced populations, based on the habitat requirements and on demographic characteristics of this species. Unlike what Boinski et al (1998) suggest, in Panamá the efforts of management should have as a minimum scale of work, a metapopulation and not a local population. Burica and Renacimiento metapopulations showed a conservation priority and good management.…”
Section: Resultsmentioning
confidence: 87%
“…The survival of the squirrel monkey in Panamá depends on management practices that may include restoring the habitat, relocations, and the administration of the isolated and highly reduced populations, based on the habitat requirements and on demographic characteristics of this species. Unlike what Boinski et al (1998) suggest, in Panamá the efforts of management should have as a minimum scale of work, a metapopulation and not a local population. Burica and Renacimiento metapopulations showed a conservation priority and good management.…”
Section: Resultsmentioning
confidence: 87%
“…The distribution of Saimiri oerstedii. Based on Boinski (1985Boinski ( , 1987, Boinski et al (1998), Reid (1997), Sierra et al (2003), Matamoros and Seal (2001), Rodríguez-Luna et al (1996), and Wong (1990). Map drawn by Mark Denil and Kimberly Meek (Center for Applied Biodiversity Science, Conservation International, Washington, DC).…”
Section: Typementioning
confidence: 99%
“…S. o. oerstedii occurs along the Pacific coast of Costa Rica, from the left bank of the Río Grande de Térraba to the Osa Pensinsula, along the coast of the Golfo Dulce and the Burica Peninsula to the western part of the Chiriquí Province, mouth of the Río Fonseca, including the Archipelago of the Golfo de Chiriquí, in Panama (Hershkovitz, 1984;Boinski et al, 1998). Surveys by Baldwin (1972, 1976) recorded its presence on the Burica Peninsula, but indicated that it is now restricted to a narrow strip of scattered lowland coastal forest fragments, not extending to the type locality David, although it possibly occurred as far east as Remedios (well to the east of David) prior to the 1950s.…”
Section: S Sciureusmentioning
confidence: 99%
“…Development of a conservation plan has been difficult because S. oerstedii is not an ''umbrella'' species and prefers habitats, primarily second growth forest, different from that used by other endangered species in the regions where it is found. Boinski et al [1998] suggested focusing conservation efforts on protecting a single site or a tight cluster of sites that provide necessary corridors for troop movement. Even though the populations are at low numbers and in a small region, Boinski et al [1998] believed there was no need for reintroduction or translocation of S. oerstedii individuals.…”
Section: Conservationmentioning
confidence: 99%
“…Boinski et al [1998] suggested focusing conservation efforts on protecting a single site or a tight cluster of sites that provide necessary corridors for troop movement. Even though the populations are at low numbers and in a small region, Boinski et al [1998] believed there was no need for reintroduction or translocation of S. oerstedii individuals.…”
Section: Conservationmentioning
confidence: 99%